Integrating Islamic Contextual Authentic Materials in English Language Learning for Islamic Community Development Students - Munir, Nurasia; Sahril, Sahril; Munir, Bayanudin (STAIN Majene, 2025)
Authentic materials are learning materials that are not specifically created for educational purposes but are used in the real world, such as texts, audios, videos, and other sources (Fitria, 2022; Fitriana et al., 2019). Integrating Islamic contextual authentic material into English language learning can help students develop English language skills while strengthening their understanding of Islamic values in a global context. This study examines the integration of Islamic contextual authentic materials into English Language Learning for students of Islamic Community Development at the State Islamic University (UIN) Datokarama Palu, Indonesia. Using a qualitative descriptive design, data were collected through classroom observations and semi-structured interviews with two lecturers and nineteen students. The findings indicated that authentic materials grounded in Islamic contexts, such as the Qur’an and Hadith, videos, Islamic songs, and English texts on social issues related to Islamic themes, enhance students’ motivation, improve their linguistic skills, and strengthen their spiritual identity. However, challenges include a lack of suitable materials and difficulty balancing linguistic authenticity with religious sensitivity. The study recommends structured teacher training, institutional repositories of Islamic authentic materials, and curriculum guidelines aligning English learning with Islamic community development competencies.